Exploitation of Time Value of OTM Options through Fully Covered Short Strangle - Srinu, M.; Rao, Hari Govinda; Rao, P. Sanyasi; Praveena, K.V. S. (International Journal of Psychosocial Rehabilitation, 2020)
Stock markets are perceived as a fool’s paradise especially in India and more specifically by small investors. In fact they are proven wealth creators for big players and unproven for small investors. The present study is an attempt to prove that stock markets can create wealth for the small players as well. Options are derivative instruments2 which provide much more flexibility for speculation. One can combine different options to develop their own strategy to win in the market place. The logic for the big player’s success and small player’s failure is that the right strategy development and perfect execution. The researcher has developed a strategy and back tested with the past data. The objective of this study is to back test the Out of the Money hedging7 strategy for a short period using the combination of algorithmic and statistical methods to decide on its consistency & future scope for implementation. The study is made on Bank nifty weekly option contracts and significant towards retail investors as the study is only based on price action but not on any other factors like market sentiments, news, fundaments, micro or macro economics and global scenarios etc.